THE IMPLEMENTATION OF GENERAL RESOLUTION 90/21 IN THE ACCOUNTING STUDIES OF CIUDAD DEL ESTE - Ariel Ochipinti Vera, Ezequiel; Matías González Martínez, Brahian; Rosa Morel Pinto, María; Edith Jara Muñoz, Milena; Fabiola Castillo Marín, Fanny (Revista Gênero e Interdisciplinaridade, 2023)
This research work focuses on the implementation of General Resolution 90/21 in the accounting studies of Ciudad del Este, Paraguay. The general objective is to know the current situation of how work is being done with the implementation of RG 90/21, to know the opinion of each of the accounting studies and if they had to take certain measures to be able to adapt to the change that the implementation brought with it. To achieve this objective, a qualitative approach was used, with a population of 3 accounting studies corresponding to km 6, km 7, km 8 of Ciudad del Este. And a sample of 3 accountants. An interview was applied and carried out in depth to collect the necessary data. The results indicate that most accounting firms have had to take measures to adapt to the implementation of RG 90/21, such as training staff and updating accounting systems. Furthermore, it was found that the majority of those interviewed consider that the implementation of RG 90/21 has improved the transparency and traceability of information, which has allowed greater control to avoid irregularities. In conclusion, this research work provides valuable information about the implementation of RG 90/21 in the accounting studies of Ciudad del Este and may be useful for other similar studies in the future.